The Effectiveness of Cyber Notaries in Ensuring Legal Certainty of Electronic Transactions in Indonesia - Tonny Nurmala Putra; Djaja, Benny; Sudirman, Maman (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2025)
The development of information technology has driven transformation in various aspects of life, including the field of notarial services. The concept of the Cyber Notary has emerged as a solution for efficiency and effectiveness of notarial services with digital technology. However, the implementation of the Cyber Notary in Indonesia still faces several challenges, particularly in ensuring legal certainty in electronic transactions. This study aims to analyze the effectiveness of the Cyber Notary in guaranteeing legal certainty in electronic transactions in Indonesia. The research method used is normative juridical, with statutory and conceptual approaches. The findings indicate that despite the great potential of Cyber Notary implementation, there are still legal voids and regulatory inconsistencies that hinder its application. Legal reform and regulatory harmonization are required, as well as improvements in infrastructure and notary competence in information technology, in order to realize legal certainty in electronic transactions through Cyber Notary.